Agroforesty Curriculum Management at Tunas Rimba I Kindergarten Purwokerto - Pujiati, Isti; Wiyani, Novan Ardy; Purwanti, Elly (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research aims to describe the management of the agroforestry curriculum at Tunas Rimba I Kindergarten, Purwokerto. This research is qualitative. Data was collected using interview, observation, and documentation techniques. The data that has been collected is then analyzed through the data reduction, data presentation, and verification stages. The research results show four activities carried out in the agroforestry curriculum management at Tunas Rimba I Kindergarten, Purwokerto. These four activities include planning the agroforestry curriculum. These planning activities prepared an agroforestry learning schedule and a Daily Learning Implementation Plan (RPPH). Second, organizing the agroforestry curriculum. In this organization, teaching tasks are distributed, the academic calendar is prepared, the curriculum structure is prepared, and the study group is determined. Third, implementing the agroforestry curriculum, where in implementing the curriculum, agroforestry learning activities are held through intracurricular and extracurricular activities so that young children can achieve the agroforestry learning objectives set out in the RPPH. Fourth, an evaluation of the agroforestry curriculum is aimed at determining the success of teachers in implementing the agroforestry curriculum.